The Effort Of Will Salas To Defend Time Reflected In Andrew Niccol's In Time Movie (2011) : An Individual Psychological Approach - Pertiwi, Ening; , Drs. H. Abdillah Nugroho, M.Hum; , Nur Hidayat, S.Pd (2013)
The research is proposed to analyze how the effort to defend time reflected in In Time movie 2011 by Individual Psychological Approach. There are two objective: the first is to analyze the movie in term of structural elements, and the second is to analyze the movie based on the individual Psychological Perspective. This study is a qualitative study, using Andrew Niccol's In Time movie 2011 as of structural elements, and the secondary data. The primary data source is In Time movie which is directed by Andrew Niccol, and the secondary data are some articles, book of literary and internet related to the subject. The method of collecting data in this research is library research by watching the movie, reading some related books and articles, accessing internet, taking notes of important part, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows that the movie illustrates the effort to defend time. The time here is used as money. The people work to get time, buy and pay everything use time. And it shows that the rich people will be immortal, the poor people will die.